Characterization of the Trans Watson-Crick GU Base Pair Located in the Catalytic Core of the Antigenomic HDV Ribozyme - Lévesque, Dominique; Reymond, Cédric; Perreault, Jean-Pierre (PLOS ONE, 2012)
The HDV ribozyme’s folding pathway is, by far, the most complex folding pathway elucidated to date for a small ribozyme. It includes 6 different steps that have been shown to occur before the chemical cleavage. It is likely that other steps remain to be discovered. One of the most critical of these unknown steps is the formation of the trans Watson-Crick GU base pair within loop III. The U23 and G28 nucleotides that form this base pair are perfectly conserved in all natural variants of the HDV ribozyme, and therefore are considered as being part of the signature of HDV-like ribozymes. Both the formation and the transformation of this base pair have been studied mainly by crystal structure and by molecular dynamic simulations. In order to obtain physical support for the formation of this base pair in solution, a set of experiments, including direct mutagenesis, the site-specific substitution of chemical groups, kinetic studies, chemical probing and magnesium-induced cleavage, were performed with the specific goal of characterizing this trans Watson-Crick GU base pair in an antigenomic HDV ribozyme. Both U23 and G28 can be substituted for nucleotides that likely preserve some of the H-bond interactions present before and after the cleavage step. The formation of the more stable trans Watson-Crick base pair is shown to be a post-cleavage event, while a possibly weaker trans Watson-Crick/Hoogsteen interaction seems to form before the cleavage step. The formation of this unusually stable post-cleavage base pair may act as a driving force on the chemical cleavage by favouring the formation of a more stable ground state of the product-ribozyme complex. To our knowledge, this represents the first demonstration of a potential stabilising role of a post-cleavage conformational switch event in a ribozyme-catalyzed reaction.